Revista de Filología Española, Madrid, t. LXIII, cuads. 3-4, julio-diciembre de 1983, y t. LXIV, cuads. 1-2, enero-junio, y 3-4, julio-diciembre de 1984. - Figueroa Lorza, Jennie (Thesavrvs, 2023)
Reseña de revistas.